PENGASUHAN DAN PENGEMBANGAN KESEHATAN ANAK USIA DINI - Erida Erida (Universitas Islam Negeri Imam Bonjol Padang, 2018)
Early age is the most important and fundamental initial period throughout the span of growth and development of human life. At this time it was marked by various important fundamental periods in the life of the next child until the final period of its development. One of the periods that characterizes early age is the Golden Ages or the golden period. This period only lasts one time in a lifetime, for that we need a basic pattern and concept of care, education, maintenance of adequate health and nutrition for early childhood, so that parents or other adults can develop their children's potential optimally. Thus, in the future children can meet the future with enthusiasm and confidence